The Sports Tourism Industry Management Model for Sustainable Development in Chengdu, China - Zhang, Yu; Piromkam , Bunjob; Phonsri , Nuttavut; Piromkam , Passapong (Journal of Roi Kaensarn Academi, 2024)
From the situation of sports tourism in China in recent years, the sports tourism industry has developed rapidly, but there are also many problems and shortcomings. The same is true for the sports tourism industry in Chengdu city, which is closely related to the sports tourism industry management model for sustainable development. The purpose of this study is to: (1) To study the current situation and influencing factors of the sports tourism industry management for sustainable development in Chengdu, China. (2) To analyze the positive factors influencing the sports tourism industry management model for sustainable development in Chengdu, China. (3)To examine and evaluate the sports tourism industry management model for sustainable development in Chengdu, China. This study adopted a mixed research method that combines quantitative and qualitative methods. Step 1: In the qualitative research section, expert was used to investigate the current situation and influencing factors of the sports tourism industry management model for sustainable development in Chengdu, China. total of 15 participants. The tool used in this study is a structured interview. Step 2: In the quantitative research section, data was collected through distributing questionnaires. and analyzed using structural equation modeling (SEM). The sample consisted of 365 respondents and was obtained through sampling. Use the method used to determine that the sample size is 20 times the inventory variable to calculate the sample size. Step 3: Through a combination of quantitative and qualitative research, 13 experts conducted focus group discussions and scoring. Experts have conducted a high-level evaluation of the feasibility, suitability, usefulness, and accuracy of the sports tourism industry management model for sustainable development in Chengdu, China. The research results indicate that: (1) The organizational structure of sports tourism in Chengdu has gradually matured, policy development has gradually improved, financial funds have continued to increase, infrastructure has been significantly improved. By comprehensively analyzing these factors, the management level of sports tourism industry in Chengdu, China can be further improved, and its sustainable development can be promoted. (2)The research results show that Resource has a significant positive impact on the sports tourism industry management model for sustainable development in Chengdu, China(P=0.000<0.05). Human operations have a significant positive impact the sports tourism industry management model for sustainable development in Chengdu, China (P=0.000<0.05).Marketing strategy have a significant positive impact on the sports tourism industry management model for sustainable development in Chengdu, China (P=0.000<0.05).Organizational structure has a significant positive impact on the sports tourism industry management model for sustainable development in Chengdu, China (P=0.000<0.05).Life cycle has a significant positive impact on the sports tourism industry management model for sustainable development in Chengdu, China (P=0.000<0.05).(3) Experts unanimousil agree that the sports tourism industry management model for sustainable development in Chengdu, China is Feasibility, Useful, Appropriate, Accuracy in A lot level-The most level.